2015
DOI: 10.4236/epe.2015.74013
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Kinetics of Jatropha Oil Transesterification

Abstract: Kinetics of a chemical reaction provides an important means of determining the extent of the reaction and in reactor designs. Transesterification of jatropha oil with methanol and sodium hydroxide as a catalyst was conducted in a well mixed reactor at different agitation speeds between 600 and 800 rpm and temperature range between 35˚C and 65˚C. The effect of variation of temperature and mixing intensity on rate constants were studied. The initial mass transfer controlled stage was considered negligible using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The Arrhenius equation demonstrates the correlation between temperature and the reaction rate constant, as stated in equation (9). Since the value of k4 (Table 3) was mostly zero for reaction at temperature 90 to 120 °C, it can be concluded that reaction (2) is irreversible.…”
Section: Reaction Rate Constant and Arrhenius Parametersmentioning
confidence: 93%
See 2 more Smart Citations
“…The Arrhenius equation demonstrates the correlation between temperature and the reaction rate constant, as stated in equation (9). Since the value of k4 (Table 3) was mostly zero for reaction at temperature 90 to 120 °C, it can be concluded that reaction (2) is irreversible.…”
Section: Reaction Rate Constant and Arrhenius Parametersmentioning
confidence: 93%
“…The relationship between temperature and reaction rate constant was shown by the Arrhenius Equation ( 9). (9) where, k is the reaction rate constant, A is the exponential factor, Ea is the activation energy, R is the ideal gas constant, and T is the reaction temperature. From the Arrhenius Equation ( 9) it can be linearized as in Equation ( 10), so that the value of the activation energy (Ea) and the exponential factor (A) can be obtained.…”
Section: Reaction Kinetics Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…It proves that temperature changes influence reaction kinetics. Temperature is a crucial external parameter in a macroscopic approach, where the reaction temperature has an exponential relationship with the reaction rate constant (Okullo & Temu, 2015).…”
Section: Resultsmentioning
confidence: 99%